Implementing a Risk-Based Hiring System Using the Spiral Model at PT. Indonesia Gadai Oke - Muhammad Adam Gozali; Martiano (CV. ADMITECH SOLUTIONS, 2025)
This study aims to address the inefficiencies and risks in the manual recruitment process at PT. Indonesia Gadai Oke, which often leads to data inconsistency, document loss, and subjective evaluations. To overcome these challenges, a Hiring Management System was developed using the Software Development Life Cycle (SDLC) with a Spiral Model approach that emphasizes risk analysis and mitigation throughout the development process. The system’s effectiveness was evaluated by applying Failure Mode and Effect Analysis (FMEA) both before and after its implementation to identify, assess, and prioritize risks based on the Risk Priority Number (RPN). The results show that the implementation of the risk-based Hiring Management System significantly reduced the RPN across all recruitment stages — the highest initial RPN in the manual process, which was 336 (for application reception), decreased to 60 after system implementation. This indicates that the system effectively minimizes potential failures, increases efficiency, and enhances objectivity in the recruitment process. In conclusion, the risk-based Hiring Management System developed using the Spiral Model and evaluated through FMEA has proven effective in mitigating critical risks and improving the overall recruitment process at PT. Indonesia Gadai Oke.